Fine-sized Pt nanoparticles dispersed on PdPt bimetallic nanocrystals with non-covalently functionalized graphene toward synergistic effects on the oxygen reduction reaction - Cho, Kie Yong; Yeom, Yong Sik; Seo, Heun Young; Lee, Albert S.; Do, Xuan Huy; Hong, Jun Pyo; Jeong, Hae-Kwon; Baek, Kyung-Youl; Yoon, Ho Gyu (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
To data, combination of Pt-based bimetallic nanocrysatals and the graphene support have significantly contributed to enhance the oxygen reduction reaction (ORR) performance relative to electrocatalysts based on monometallic Pt nanoparticles (NPs) primarily due to the unique ligand effects and benefits of the carbon support. In this study, we propose a new structure of bimetallic electrocatalysts to realize the synergistic effects on the ORR performance through effective integration of the fine-sized Pt NPs, PdPt bimetallic nanocrystals, and non-covalently functionalized graphene with ionic polymers. The facile wet-chemical methods were applied to synthesize fine-sized (2-5 nm) spherical Pt NPs doped large-sized (20-50 nm) non-spherical PdPt bimetallic NPs on the electronically negative ionic polymer-functionalized graphene support (Pt-on-PdPt/fG). This Pt-on-PdPt/fG with synergistic effects based on enlarged active surface area, ligand, and interfacial linking effects, exhibits substantially enhanced ORR activity (specific activity: 1.89 mA cm(Pt)(-2) at 0.9 V-RHE) and durability in comparison to the commercial Pt/C (specific activity: 0.23 mA cm(Pt)(-2) at 0.9 V-RHE). To this end, the effective integration of newly designed fine-sized Pt NPs doped bimetallic nanocrystals and unique graphene supports with the well-interactive ability could be a good platform to develop the advanced electrocatalysts for the efficient ORR. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: MEMBRANE FUEL-CELLS; BY-LAYER DEPOSITION; PLATINUM NANOPARTICLES; BLOCK-COPOLYMER; PARTICLE-SIZE; SHELL-PD; CATALYSTS; ELECTROCATALYSTS; NANOCUBES; SHAPE